2018
DOI: 10.1080/14767058.2018.1463986
|View full text |Cite
|
Sign up to set email alerts
|

The role of prophylactic internal iliac artery ligation in abnormally invasive placenta undergoing caesarean hysterectomy: a randomized control trial

Abstract: Bilateral internal iliac artery ligation, in cases of AIP undergoing caesarean hysterectomy, is not recommended for routine practice to minimize blood loss intraoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 26 publications
2
22
0
1
Order By: Relevance
“…Our study found that using prophylactic IIAL has no statistically significant role in reducing the mean blood loss and the mean transfused blood products in placenta percreta patients before CH with the use of blunt dissection technique. These findings are compatible with those of former studies that examine utilizing prophylactic bilateral IIAL before CH in patients with abnormally invasive placenta [7,8] and only placenta percreta [9]. Kuhn et al retrospectively found that bilateral IIAL in patients with placenta percreta undergoing CH did not significantly decrease the amount of blood loss in 11 patients when compared to 26 patients without bilateral IIAL [9].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study found that using prophylactic IIAL has no statistically significant role in reducing the mean blood loss and the mean transfused blood products in placenta percreta patients before CH with the use of blunt dissection technique. These findings are compatible with those of former studies that examine utilizing prophylactic bilateral IIAL before CH in patients with abnormally invasive placenta [7,8] and only placenta percreta [9]. Kuhn et al retrospectively found that bilateral IIAL in patients with placenta percreta undergoing CH did not significantly decrease the amount of blood loss in 11 patients when compared to 26 patients without bilateral IIAL [9].…”
Section: Discussionsupporting
confidence: 88%
“…Although a hysterectomy is the most preferred surgical procedure [4], bilateral internal iliac artery ligation (IIAL) technique has been performed as a life-saving modality to decrease haemorrhage in obstetrical and pelvic surgeries when other commonly used surgical methods fail [5,6]. There are only a few studies about using bilateral IIAL during abnormally invasive placenta [7,8] and only placenta percreta surgery [9] which are mostly designed with a limited number of patients. Blunt dissection technique with index finger is a new surgical method to reduce bleeding in the vesico-uterine pouch and to avoid bladder injury during CH in patients with placenta percreta that invades posterior bladder wall [10].…”
Section: Introductionmentioning
confidence: 99%
“…Since balloon catheters and sheaths are inserted, it is easy to perform additional uterine artery embolization immediately in the case of uncontrolled bleeding after cesarean delivery. In contrast, bleeding control may take longer with surgical ligation use; thus, the prophylactic use of bilateral internal iliac artery ligation has been found to have limited advantages in the reduction of inter-operative bleeding rates [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In low-resources countries, where IR is not available it has remained in use in particular in the context of uterine preservation in PAS. A recent RCT of bilateral internal iliac artery ligation (n= 29 cases) versus controls (n= 28 cases) reported no significant difference between the two groups regarding the intraoperative estimated blood loss (86).…”
Section: Additional Therapeutic Techniquesmentioning
confidence: 91%